Representationalism can connect neuroscience and philosophy - Kok, Albert (Frontiers in Cognition, 2026)
Representationalism is the theory that our conscious perception of the world is mediated by mental representations, rather than being a direct encounter with reality. In this article, we define representations in terms of a unified theory of long-term memory that incorporates both its explicit and implicit divisions. Apart from these integrative features, the theory offers the possibility for reconciling perspectives in neuroscience and the philosophy of mind. We address various areas of debate, focusing on concepts such as consciousness, intentionality, emergence, and qualia. We draw the following conclusions based on our framework applied to representational systems. First, conscious experience results from the retrieval of the contents of explicit memory representations from short-term memory. Regarding intentionality, the strong link between intentionality and memory representations allows us to define intentionality, capturing both the “what is it” and “what it is like” aspects. Finally, notions referring to the subjective experiential content of consciousness, such as emergence and “qualia”, are integral to all conscious experience, reflecting memory-emotion interactions realized in neuro-affective networks. Ultimately, we conclude that concepts from the philosophy of mind can be harmonized, in a non-reductionist way, with neurocognitive theories that define memory representations as multilevel networks of large-scale brain systems.